Does the ethnic density effect extend to obesity? A cross-sectional study of 415 166 adults in east London. Issue 5 (1st June 2019) - Sutaria, Shailen; Mathur, Rohini; Hull, Sally A
Abstract : Objectives: To examine the prevalence of obesity by ethnic group and to examine the association between ethnic density and obesity prevalence. Design and setting: Cross-sectional study utilising electronic primary care records of 128 practices in a multiethnic population of east London. Participants: Electronic primary care records of 415 166 adults with a body mass index recorded in the previous 3 years. Outcome measures: (1) Odds of obesity for different ethnic groups compared with white British. (2) Prevalence of obesity associated with each 10% increase in own-group ethnic density, by ethnic group. Results: Using multilevel logistic regression models, we find that compared with white British/Irish males, the odds of obesity were significantly higher among black ethnic groups and significantly lower among Asian and white other groups. Among females, all ethnic groups except Chinese and white other were at increased odds of obesity compared with white British/Irish. There was no association between increasing ethnic density and obesity prevalence, except among black Africans and Indian females. A 10% increase in black ethnic density was associated with a 15% increase in odds of obesity among black African males (95% CI 1.07 to 1.24) and 18% among black African females (95% CI 1.08 to 1.30). Among Indian females, a 10% increase in Indian ethnic density was associated with a 7% decrease in odds of obesity (95% CI 0.88 to 0.99). Conclusion: Wider environmental factors play a greater role in determining obesity than the ethnic composition of the area for most ethnic groups. Further research is needed to understand the mechanism through which increasing ethnic density is associated with increased odds of obesity among black Africans and decreased odds of obesity among Indian females.